MAKNA SIMBOLIK TARI SONTOLOYO GIYANTI KABUPATEN WONOSOBO (Jurnal Seni Tari, 2013)
Sontoloyo dance is a traditional dance that became the basis of  the dance mask dance Leng- ger Giyanti. This dance contains a mockery of  the fragility of  the ruler as well as religious symbols of  Islam. The purpose of  this study to understand and describe the symbolic mea- nings that exist in Sontoloyo dance. This study is qualitative and descriptive research. The collection of data using observation techniques, interviews and documentation. Data analysis was performed by means of  data reduction, data presentation, the validity of  the data using triangulation of  data and drawing conclusions. The results show that dance is a traditional dance popular Sontoloyo depicting the valor of soldiers. Dance Sontoloyo have symbolic mea- ning contained in the motion, songs, property and accompanying music. Motion used in the dance Sontoloyo is: mincet, lampah sekar, jinjitan, golekan, ngencek, blows and move sekar pacak Gulu. Dance has some symbolic meaning, that is: religious meaning, the meaning of solidarity and mutual cooperation, the meaning of knights and responsibilities, as well as the meaning of satire against the ruling. Sontoloyo accompaniment of dance has a meaning: the compactness   and   the   knights,   and   responsibility,   and   innuendo.    Sontoloyo   dance makeup implies: valor and courage, beauty and  neatness. Sontoloyo fashion dance has a meaning:  a person’s  status,  accuracy,  authority,  and  valor,  satire  and  beauty.  Fashion colors have mea- ning:  a  protest  against  the  arbitrariness  of   the  authorities,  sarcasm, happiness, anger  and turmoil liver.